Theory-informed process evaluation protocol to assess a rapid-access outpatient model of care in South East Queensland, Australia - Hannah E Carter; Steven M McPhail; Shannon Wallis; Kelly McGowan; Sundresan Naicker; Ashleigh Earnshaw (BMJ Open)
Introduction Chronic diseases place a large burden on health systems globally. While long-term planned care is essential for their management, episodes of deterioration are common. The emergence of rapid access to outpatient care has proliferated in response to increased resource pressures on acute health services. It is anticipated that these new models of care may prevent hospitalisations and reduce the burden on emergency departments. While some evidence supports the clinical effectiveness of these models, little is known about the core components and key attributes of these services. This paper outlines the protocol of a theory-driven, pragmatic process evaluation embedded within a new rapid-access outpatient service for chronic disease in South East Queensland, Australia.Methods and analysis This mixed-methods process evaluation will be conducted across three phases: (1) context assessment to identify programme characteristics and core components; (2) evaluation of key service processes and development of service improvement strategies and (3) sustainability assessment, with a focus on programme embedding and the resources associated with service evaluation. Each phase will be guided using implementation science frameworks and/or theory. Participants will include service consumers, service delivery staff, implementation leaders and decision-makers and wider system referrers. Professional stakeholders will be recruited through a direct invitation to participate (using purposeful sampling methods) and will be engaged in interviews at 1–3 data collection time points. Service consumers will be recruited through direct advertisement to participate in interviews. Administrative and clinical data collections will be retrospectively analysed with descriptive and inferential methods and triangulated with qualitative data to yield primary and secondary outcomes.Ethics and dissemination Ethical clearance has been obtained from the West Moreton Hospital and Health Service Human Research Ethics Committee. The planned dissemination of results will occur through conferences, abstracts and publications.Trial registration number Australia and New Zealand Clinical Trials Registry (ANZCTR Trial ID: ACTRN12624000757516).